2013
DOI: 10.5586/aa.1982.010
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical changes in the stems of highbush blueberry (Vaccinium australe Small), caused by the fungus Godronia cassandrae f. vaccinii (Peck) Groves

Abstract: Some histological changes were observed in blueberry stems infected by the fungus G.cassandrae. Dead cells of subepidermal collenchyma and cortical parenchyma filled with brown flocculent deposits were seen in the lesion areas. Pycnidia characteristic for the conidial stage of the fungus (Topospora myrtilli) were found in the collenchyma layer. The diseased tissues were found to be separated from the healthy ones by a layer of cork cells which was initiated under the epidermis and ended under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In classical phytopathological studies of various pathogens, research begins with the observation of the development of the disease (symptoms and etiological signs). The observations made during the presented studies fully confirmed the earlier findings of various Polish researchers from the last 50 years [ 16 , 18 , 30 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Similar results have also been obtained outside Poland and even outside Europe [ 4 , 13 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In classical phytopathological studies of various pathogens, research begins with the observation of the development of the disease (symptoms and etiological signs). The observations made during the presented studies fully confirmed the earlier findings of various Polish researchers from the last 50 years [ 16 , 18 , 30 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Similar results have also been obtained outside Poland and even outside Europe [ 4 , 13 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
“…Neither the type of disease symptoms (even if the etiological signs of the pathogen are present) nor anatomical examinations of infested stems allow proper and complete diagnosis of the pathogen [ 29 , 30 ]. For full mycological identification of the causal agent, analysis using artificial culture methods as well as molecular biology methods is necessary [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%